2014
DOI: 10.2139/ssrn.2186818
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Effects of Protestant Activities in China

Abstract: Does culture, and in particular religion, exert an independent causal effect on long-term economic growth, or do culture and religion merely reflect the latter? We explore this issue by studying the case of Protestantism in China during the late nineteenth and early twentieth centuries. Combining county-level data on Protestant presence in 1920 and socioeconomic indicators in 2000, we find that the spread of Protestantism has generated significant positive effects in long-term economic growth, educational deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…Together, these findings, as well as findings from other research studies (Stulz and Williamson, 2003;Barro and McCleary, 2003;Chen et al, 2014), support Weber's idea that the Protestant Constitutional Convention, 49 were Protestants (Lambert, 2003). Of course, we do not want to make any strong causal inferences from this observation, but it is clear that the formation of the American civil society was strongly influenced by Christian Protestant values (Wills, 1979;Amos, 1989).…”
Section: Figure 5: Gross National Product and Trust Level 1991supporting
confidence: 78%
See 2 more Smart Citations
“…Together, these findings, as well as findings from other research studies (Stulz and Williamson, 2003;Barro and McCleary, 2003;Chen et al, 2014), support Weber's idea that the Protestant Constitutional Convention, 49 were Protestants (Lambert, 2003). Of course, we do not want to make any strong causal inferences from this observation, but it is clear that the formation of the American civil society was strongly influenced by Christian Protestant values (Wills, 1979;Amos, 1989).…”
Section: Figure 5: Gross National Product and Trust Level 1991supporting
confidence: 78%
“…Consistent with this idea, a number of independent research studies showed that Protestants have a higher level of trust (Inglehart, 1999;Uslaner, 2002;Guiso et al, 2003;Delhey and Newton, 2005;Bjornskov, 2007) and lower level of corruption (Treisman, 2000;Guiso et al, 2003;Woodberry, 2004;Arrunada, 2010;Chen et al, 2014). Trust and honesty, of course, are important factors for economic growth.…”
Section: Social Ethic: Trust and Honestymentioning
confidence: 93%
See 1 more Smart Citation
“…Sng and Moriguchi (2014) argue that Meiji Japan's far more successful modernization in the 19th century, visá vis China, can be attributed to greater state capacity in the former.8Jia (2014) andChen et al (2014) present evidence that Western influence had persistent consequences into the late 20th century.…”
mentioning
confidence: 88%
“…These patterns demonstrate that there is indeed a positive correlation between Protestantism and wealth. In addition, researchers have shown that not only is there a positive correlation, but also causal connections (Blum and Dudley 2001, Becker and Woessmann 2009, Chen et al 2014, Rubin, 2017.…”
Section: Statistical Evidencementioning
confidence: 99%